"You Have to Be Part of the Process": A Qualitative Analysis of Older African American Men's Primary Care Communication and Participation. Issue 4 (July 2019) - Mitchell, Jamie; Williams, Ed-Dee G.; Perry, Ramona; Lobo, Kavitha
The objective of the current study was to understand older African American men's perceptions of and experiences with patient–provider communication during primary care medical visits. Fifteen African American men age 50 and older participated in individual semistructured interviews. Open-ended questions focused on their primary care therapeutic alliance, preferences for decision-making, self-efficacy, patient satisfaction, communication, and companion participation during primary care medical visits. Emergent themes included the perception of rushed and inattentive care related to low socioeconomic status, inadequate information exchange about medical testing and follow-up care, welcoming the help of highly engaged companions, and proactively preparing for medical visits. Participants' assertiveness, confidence, and persistence with health providers regarding agenda setting for their care were most prevalent and contradict extant literature portraying African American men as less engaged or informed patients. Older African American men, particularly those with low socioeconomic status, may benefit from additional support and advocacy to consistently receive patient centered care and communication.